Efficacy of Blended Learning Techniques in Medical and Dental Education: Students’ Opinions in Relation to Their Habits as Internet Consumers - Cristina Gena Dascalu; Magda Ecaterina Antohe; Claudiu Topoliceanu; Cristina David; Victor Lorin Purcarea (Applied Sciences, 2023)
The success of blended learning programmes, based on digital tools, depends on several factors that significantly influence students’ performance, of which demographics (gender and age group) are the most common. Other factors play an important role too. Among these, we focused on the students’ general attitude towards the digital environment and the importance they attach to it in their daily activities. We investigated a sample of five hundred fifty-one students from four Medical Universities in Romania, mostly females (76.2%), from years 1 and 2 of study (63.7%) and aged between 18 and 20 years (53.9%), and we recorded their general opinion about the effectiveness of four types of teaching tools and the intensity of using Internet services in their daily activities. We conducted univariate (hypothesis testing) and multivariate (two-step clustering) analyses of the recorded responses, and we found that the students’ general behaviour as the users of Internet services significantly influences their choices for certain teaching tools over others. Students who prefer classic oral presentations and PowerPoint presentations are predominantly females, aged between 18 and 20, who use Internet services mainly for communication. Students who prefer educational videos are also mainly females, evenly distributed by age groups; they enjoy using multimedia resources during learning and use Internet services for communication, information or entertainment. Students who prefer the use of online documentary sources are evenly distributed by gender and are over 20 years of age; they also enjoy using multimedia resources during learning and use Internet services mainly for communication and information. The obtained results show that, to optimally combine the teaching tools used in blended learning, it is useful to assess in advance the attitude towards the digital environment of the students to whom it is addressed.